2012
DOI: 10.1021/jm3003697
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Effects on Protein–Ligand Binding

Abstract: The effects of addition of a methyl group to a lead compound on biological activity are examined. A literature analysis of >2000 cases reveals that an activity boost of a factor of ten or more is found with an 8% frequency, and a 100-fold boost is a 1 in 200 event. Four cases in the latter category are analyzed in depth to elucidate any unusual aspects of the protein-ligand binding, distribution of water molecules, and changes in conformational energetics. The analyses include Monte Carlo/Free Energy Perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
285
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(311 citation statements)
references
References 44 publications
8
285
2
9
Order By: Relevance
“…A previous study on the effects of methyl groups in ligand–protein binding suggested that a methyl group positioned in a hydrophobic environment instead of a hydrogen may result in a 10-fold increase in potency. 49 However, to observe an effect beyond that, the methyl group should also prompt a more favorable conformational change. 49 A possible structural explanation for the pronounced effects of an alkyl substituent at the 4-and 6-positons of the pyridone ring on EZH2 inhibition is that the addition of more van der Waals contacts leads to positioning the pyridonemethyl-amide core in an optimal geometry for the hydrogen bond interactions with W624 and Y111 (Figure 3A), which in turn lowers enthalpic contribution to the free energy of binding.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study on the effects of methyl groups in ligand–protein binding suggested that a methyl group positioned in a hydrophobic environment instead of a hydrogen may result in a 10-fold increase in potency. 49 However, to observe an effect beyond that, the methyl group should also prompt a more favorable conformational change. 49 A possible structural explanation for the pronounced effects of an alkyl substituent at the 4-and 6-positons of the pyridone ring on EZH2 inhibition is that the addition of more van der Waals contacts leads to positioning the pyridonemethyl-amide core in an optimal geometry for the hydrogen bond interactions with W624 and Y111 (Figure 3A), which in turn lowers enthalpic contribution to the free energy of binding.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the changes in activity of 1−2 orders of magnitude resulting from altered methylation at this β 2 -position may be considered a prominent naturally evolved example of the so-called "methyl effect" elegantly discussed by Jorgensen and co-workers for drug-like compounds. 48 We were therefore interested in determining the root of this effect in our system and first hypothesized that the main contribution was conformational remodeling of the azumamide backbone. Somewhat to our surprise, the high-resolution NMR structures of representative ligands revealed no significant conformational variation in the macrocyclic backbone region.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…The reason for the low potency of compound 6a , which lacks any substituent at the α-position, is not currently clear, but the results suggest that an α-position substituent is critical for providing binding energy and possibly proper orientation of the inhibitor with its target protein. 31 …”
Section: Resultsmentioning
confidence: 99%